T‐cell prolymphocytic leukemia and tuberculosis: a puzzling association. Issue 9 (10th August 2017) - Cervera, Pascale; Gilhot, Amélie; Marzac, Christophe; Féger, Frédéric; Tang, Ruoping; Jaff, Nabaz; Coppo, Paul
Key Clinical Message: T‐cell prolymphocytic leukemia can result in severe immune T‐cell deficiency. Clinicians should be aware of this complication in this rare lymphoid malignancy, and opportunistic infections should be ruled out before the use of usual immunosuppressive procedures such as alemtuzumab and hematopoietic stem cell transplantation. Abstract : T‐cell prolymphocytic leukemia can result in severe immune T‐cell deficiency. Clinicians should be aware of this complication in this rare lymphoid malignancy, and opportunistic infections should be ruled out before the use of usual immunosuppressive procedures such as alemtuzumab and hematopoietic stem cell transplantation.